Bifidobacterium longum affects the methylation level of forkhead box P3 promoter in 2, 4, 6-trinitrobenzenesulphonic acid induced colitis in rats. (September 2017) - Zhang, Ming; Zhou, Lixing; Zhang, Shu; Yang, Yang; Xu, Lei; Hua, Zichun; Zou, Xiaoping
Abstract: Bifidobacterium longum ( B. Longum ) is a common probiotic colonized in the human gut and against the development of chronic inflammation including inflammatory bowel disease (IBD). But the underlying mechanism remains unknown. The aim of this study was to evaluate the affection of B. longum on the methylation levels of forkhead box P3 (Foxp3) promoter. 2, 4, 6-trinitrobenzenesulphonic acid (TNBS)-induced colitis rat models were treated with B. longum or medium, respectively. The genomic DNA of spleen peripheral blood mononuclear cells (PBMC) cells was extracted. After bisulphite treatment and pyrosequencing, the methylation levels of each CpG sites in the promoter of forkhead box protein P3 (Foxp3) were analyzed. B. Longum treatment changes the methylation level in Foxp3 promoter in TNBS-treated colitis rats, and significantly demethylates several CpG sites in Foxp3 promoter. The demethylation of Foxp3 promoter might be involved in the effectiveness of B. Longum treatment for IBD. Further research remains necessary to investigate the role of B. Longum in Foxp3 demethylation. Using B. Longum or its metabolic products is an option for further investigations on potential treatments for IBD. Highlights: B. Longum treatment changes the methylation level in Foxp3 promoter in TNBS-treated colitis rats. B. Longum significantly demethylates several CpG sites in Foxp3 promoter. The demethylation of Foxp3 promoter might be involved in the effectiveness of B. Longum treatment for IBD.